The recovery-orientation of three mental health units. Issue 3 (2nd September 2014) - Bass, Hollie; Tickle, Anna; Lewis, Nicholas
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to measure service user and staff views of the recovery orientation of three mental health rehabilitation units; two "open" and one "locked". It identified elements of recovery that were important to service users. It measured the units' performance on domains of recovery, attending to differences between staff members' and service users' perceptions and between the locked and open units. Design/methodology/approach – A cross-sectional design was used. Staff and service users completed the "Developing Recovery Enhancing Environment Measure (DREEM)". Findings – Findings revealed some differences between staff and service user views. Service users in the locked unit reported the organisational climate to be more recovery oriented on some domains than those in the open units. Service users' responses highlighted potential areas for service improvement. Research limitations/implications – The sample was small but reflected the applied setting. Some service users were not invited to participate because of significant communication or cognitive difficulties and it is recognised that they may have had alternative views that remain unrepresented. Practical implications – The DREEM provided valuable information about current practice and potential for service development. Both locked and open units can provide recovery-oriented environments. Services should be aware of discrepant views between staff and service users. Originality/value – To the knowledge, this is the first study to use the DREEM to evaluate the recovery orientation of a locked recovery unit and to compare locked and unlocked units.